SALE DIDACTIC PRINCIPLES OF CLARITY IN ALGORITHMIC PREPARING STUDENTS IN THE CONDITIONS OF INFORMATIVELY-COMMUNICATION PEDAGOGICAL ENVIRONMENT - Voloshinov, C.A. (Journal of Information Technologies in Education (ITE), 2011)
The paper investigated the development of the theory of visual learning, the functions and features of the visibility of the principle of clarity in the modern educational process. Set are the notion of "visual learning environment" and the didactic significance of interactive multimedia process visualization, investigate the problem of identifying potential cognitive visualization in algorithmic training students to use information and communication teaching environment.